Text, Reader, and the Fusion of the “I” In Edgar Allan Poe’s “Alone” - Shajwan Nariman Fatah; Ala Beshank Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Edgar Allan Poe’s Alone has been read biographically, various critics analyzed this poem as a reference to the poet’s psychological issues related to his childhood; his troubled relations with his parents. However, the aim of this paper is to put such readings aside, instead, the researchers attempt to have a close analysis and exclude the external agents. Through semiotic reading, this study unravels the words and explores the other side of significations, then relate the interpretation to literary theories. In the discussion, the analysis shows the integration of the text with the reader through the narrative “I,” the phenomenological theory of reading (Georges Poulet,) and then connect the findings to the works of major theorists of post-structuralism: Jacques Derrida and Roland Barthes.